The convenience of takhrij al-hadith through ICT apps: An exploratory analysis on selected hadith website and mobile apps - Suliaman, Ishak; Zulkipli, Shahril Nizam; Muhamad Ramlan, Anaztasia Natasha; Anas, Norazmi; Ahmat, Amin Che; Aziz, Nurul Hidayah; Zaki Yaakob, Mohd Ashrof (IAEME Publication, 2018)
The development of information and communications technology (ICT) has given a new dimension to the study of hadith in cyberspace as an effort to empower, uphold and preserve it in a long run. Thus, this study’s focused on three mobile apps which are Encyclopedia of 9 Imam, Mawsu‘ah al-Hadith al-Nabawi al-Sharif and Kutub Tis’ah along with three websites, namely al-Durar al-Saniyyah, Mawqi’ al-Islam and Islamweb that can be used to facilitate takhrij hadith. The study is aims to demonstrate the convenience of takhrij hadith in ICT integration and explore some of ICT apps that can be utilized to assist learning. Methodology applied was a qualitative method of hadith data collection infused within the apps. It was later revealed that a few of takhrij facilities were instilled in these apps: (1) Source of hadith (2) Ranking of hadith (3) Sanad hadith (4) Matan hadith (5) Rating of hadith in other sources (to specify Syawahid/Mutaba‘at) (6) The biography of narrators (al-Jarh wa al-Ta’dil) (7) Types of hadith based on the Sanad (8) Types of hadith based on Matan (9) Hukm al-Hadith. The study found that as many as nine takhrij facilities have been infused in all of the six ICT apps. Encyclopedia of 9 Imam apps is the leading apps so far that can be useful for scholars, for it contained all the facililities mentioned. Nevertheless, to go on hadith search through available websites is much more extensive as they provide access to a larger amount of hadith.